Thin films of vinylidene fluoride copolymer with tetrafluoroethylene: dynamics of ferroelectric polarization switching - Fedosov, S. N.; Sergeeva, A. E. (Physics and Chemistry of Solid State, 2020)
The vinylidene fluoride copolymer with tetrafluoroethylene P(VDF-TFE) is a typical ferroelectric polymer that has not been sufficiently studied so far in comparison with pure polyvinylidene fluoride (PVDF) and its copolymer with trifluoroethylene. The purpose of this work was to reveal the features of forming ferroelectric polarization and its switching in thin films of P(VDF-TFE) under various conditions, such as the level of the applied electric field and the duration of its action within 8 orders of magnitude from 10 μs to 100 s. The sequence of voltage pulses applied during poling and polarization reversal allowed to reveal the characteristics of the polarization switching dynamics. To increase the resolution of the measurements, two complementary methods of recording electrical induction were used. The features of polarization and space charge relaxation over time have been studied by thermally stimulated depolarization method. A new phenomenon of gradual separation of the relaxation processes associated with polarization and space charge was observed. Both components were accompanied by trapped charges that compensated the depolarizing field. Several practical recommendations have been formulated regarding the desirable values of poling parameters and additional processing to increase the ferroelectric polarization stability.